USING ROLE-PLAYING GAMES TO ORGANIZE ENGLISH LESSONS IN PRESCHOOL EDUCATION (Ustozlar uchun, 2025)
This article discusses the importance, didactic possibilities, and pedagogical advantages of using role-playing games in teaching English in preschool education. Role-play is presented as an effective tool for increasing children's speech activity, developing communication skills, improving listening comprehension, and expanding vocabulary. Methodological recommendations and practical examples are also provided.